Principles Of EFL Instruction With An Islamic Perspectives - Kalayo Hasibuan Hasibuan; Muhammad Syahrul Syahrul; Nailul Husna Husna; Nur Aliyah Aliyah (Journal of Innovative and Creativity, 2025)
This paper explores integrating English as a Foreign Language (EFL) instruction with Islamic perspectives, drawing upon various sources to illustrate effective strategies. The discussion centers on embedding Islamic values within learning materials and activities, utilizing English to promote Islamic understanding, and cultivating students' ability to communicate effectively across diverse cultural and religious contexts. The paper examines challenges and proposes solutions for implementing this approach within Islamic educational institutions, aiming to foster linguistically proficient, spiritually aware, and ethically grounded learners. Specific strategies discussed include utilizing authentic materials reflecting Islamic values (e.g., Quranic verses, Hadith, Islamic literature), incorporating culturally sensitive pedagogical approaches that respect diverse learning styles and communication preferences, and designing activities that promote critical thinking and ethical decision-making within an Islamic framework. The study also addresses challenges such as the potential conflict between Western cultural norms embedded in some EFL materials and Islamic values, and the need for teacher training in culturally responsive pedagogy. By analyzing successful models of EFL instruction within Islamic contexts and drawing upon relevant theoretical frameworks, such as the Spiral Andromeda Philosophy, the paper offers practical recommendations for developing effective and holistic EFL curricula that align with the goals of Islamic education. The research highlights the potential of this integrated approach to not only enhance students' linguistic proficiency but also to nurture their spiritual growth, moral development, and intercultural understanding.